The undrained shear strength of soft clay reinforced with single ceramic waste column - Mohamad Laziem Jameel, Mohd Sofe (2017)
Nowadays, due to limited availability of construction sites, developers take an effort to construct a building on a soft clay soil. Ground improvement methods are used to reduce the weakness of soft clay which is low strength and high compressibility characteristics. Stone column is a method where some of the soil is being replaced with granular material such as crushed rocks or sand. The stone column technique is a very efficient method of improving the strength parameters of soil like bearing capacity and reducing consolidation settlement. Ceramic waste being used as substitute of fine aggregate as it has almost similar properties as sand. An effective utilization of ceramic waste in construction materials will significantly reduce the accumulation of the by product in landfills and thus reduce environmental pollution. This study is to determine the undrained shear strength of soft clay reinforced with 10 mm and 13 mm diameter single ceramic waste column with various lengths. The first stage of the study was determination of the physical and mechanical properties of the material used such as soft clay and ceramic waste. At the second stage, three batches of samples with each batch consists of five samples were prepared by using compaction method. All specimens of 50 mm in diameter and 100 mm in height soft kaolin clay with single ceramic waste columns with various lengths which are 60 mm, 80 mm, and 100 mm was subsequently tested under Unconfined Compression Test. The result shows that the shear strength of samples increases as the height and volume of ceramic waste column increases.